Physico-Chemical Properties of Corn Bread Fortified with Moringa Leaves (Moringa oleifera) Flour - Maria Susana Medho; Endeyani V. Mohamad (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
This study aimed to examine the effect of Moringa leaf flour concentration on the physical and chemical properties and level of preference of Moringa corn bread. The study was conducted with variations of Moringa leaf flour concentration (TK): TK1 = 1%; TK2 = 3%; TK3 = 5%; TK4 = 7%. Parameters to be analyzed included physical properties, namely bread volume, specific volume of bread and bread elasticity. Chemical properties included water content, protein, vitamin C, β-karoten. The results showed that the highest macro- and micronutrient values in the addition of 7% Moringa leaf flour was inversely proportional to the physical properties of the bread, namely a decrease in the specific volume and elasticity of Moringa cornbread which resulted in a decrease in panelists' acceptance of Moringa cornbread products. TK3 was the best with protein value of 7.27 mg/100g, vitamin C 60.0 mg/100g, β-karoten 13909.99 µg/100g, specific volume of bread 3.71 cm3/g and bread elasticity. 75.14% and the highest sensory acceptance of moringa cornbread. Keyword: Physical, Chemical, Bread, Corn, Moringa